ZeroProKeS: A Secure Zeroconf Key Establishment Protocol for Large-Scale Low-Cost Applications - Sakib, Shahnewaz Karim; Amariucai, George T; Guan, Yong (IEEE transactions on dependable and secure computing, 2023)
Traditional approaches to authenticated key establishment include the use of PKI or trusted third parties. While certificate deployment is sub-optimal for large-scale, low-cost applications, the use of trusted third parties is subject to human error and leaked credentials. For this context, co-location can be a valuable resource, and it is often exploited through common randomness harvesting techniques, but these, in turn, suffer from low achievable rates and usually from restrictive assumptions about the environment. Recent techniques for exploiting co-location are based on the notion of quality time and rely on sophisticated throttled clue-issuing mechanisms that allow a device with enough time to spend in the vicinity of the transmitter to find a secret key by collecting enough consecutive clues. By contrast, attackers are afforded only limited time to listen to, or interact with, the clue transmitter. Previous work in this direction deals solely with passive attackers and uses high-overhead information throttling mechanisms. This paper introduces the active attacker model for the quality-time paradigm and proposes a simple solution, a Zeroconf Key Establishment Protocol (ZeroProKeS). Additionally, the paper shows how to efficiently expand the proposed protocol to adhere to any customized information transfer function between legitimate users.